Ground improvement and geosynthetics : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Puppala, Anand J. (American Society of Civil Engineers : Geo-Institute, 2010)
Proceedings of sessions of GeoShanghai 2010, held in Shanghai, China, June 3-5, 2010. This Geotechnical Special Publication contains 48 papers presenting the most current research on ground improvement and geosynthetics. Topics include: ground improvement, especially with regard to unstable ground; soft soils; expansive soils; collapsible soils; reclaimed soils; contaminated soils; and others. Papers analyze improvement methods including mechanical and hydraulic methods, chemical stabilization methods in both shallow and deep ground, and reinforcement methods using geosynthetics. -- Provided by publisher.
"Hosted by Tongji University; Shanghai Society of Civil Engineering, China; Chinese Institution of Soil Mechanics and Geotechnical Engineering, China; in cooperation with Alaska University Transportation Center, USA; ASCE Geo-Institute, USA; Deep Foundation Institute, USA; East China Architectural Design & Research Institute Company, China; Georgia Institute of Technology, USA; Nagoya Institute of Technology, Japan; Transportation Research Board (TRB), USA; The University of Newcastle, Australia; The University of Illinois at Urbana-Champaign, USA; The University of Kansas, USA; The University of Tennessee, USA; Vienna University of Natural Resources and Applied Life Sciences, Austria."
Keywords: Soil stabilization -- Congresses.; Geosynthetics -- Congresses.; Earthwork -- Materials -- Congresses.; elektronické knihy; electronic books